Influence of time-domain detection algorithm-based motion biological image analysis on selecting suitable receiving area - Viciana, C.; Jones, P. (Malaysian Sports Journal, 2019)
To comprehensively understand the variations in the joint angles and center of gravity under different suitable receiving situations of badminton. By constructing a time-domain detection algorithm, the variations in the joint angles and gravity center of joints in three different receiving areas are analyzed: (1) the right shoulder, elbow, and right wrist joint angles of forehand receiving in front of the net; (2) the right wrist and right shoulder joint flexion-extension angels and the right elbow joint angle of backhand receiving in front of the net; and (3) the variations in center of gravity during high-shuttle receiving in front of the net. By quantifying the joint angles, the rationality of the selected area is determined. The results show that the proposed time-domain detection algorithm is accurate in judging the joint angles of the shoulder, elbow, and wrist under different receiving situations. As for the variations in joint angles of both forehand and backhand receiving in front of the net and the center of gravity during high-shuttle receiving, the judgments are close to the standard values. Also, the algorithm shows excellent stability while selecting the receiving areas. Based on the time-domain detection algorithm, the angle variations in the shoulder, elbow, and wrist joints in three different receiving areas are judged and selected,which provides suggestions for badminton training. The proposed algorithm is highly accurate and stable in selecting receiving areas in different situations. Also, selecting the shoulder, elbow, and wrist joint angles during exercise requires comprehensive consideration of multiple factors. A single parameter cannot make an accurate selection. The results have greatly improved the recognition of time-domain detection algorithm and joint angle variations while receiving the shuttle